Effect of L-arginine and sildenafil citrate on intrauterine growth restriction fetuses: a meta-analysis. Issue 1 (December 2016) - Chen, Juncao; Gong, Xiaoyuan; Chen, Pingyang; Luo, Kaiju; Zhang, Xiuquan
Abstract Background Intrauterine growth restriction (IUGR) is associated with perinatal morbidity and mortality. Several clinical trials have reported L-arginine and sildenafil citrate had effect on intrauterine growth restriction fetuses. A meta-analysis of available randomized controlled trials (RCTs) was conducted to investigate the effects of L-arginine and sildenafil citrate on major clinical outcomes of IUGR fetuses. Methods Systematically searched Medline, Embase, the Cochrane Library, and Clinical Trials, references of retrieved articles, and conference proceedings from 1960 to 2015. We included randomized controlled trials assessing the effects of L-arginine and sildenafil citrate on IUGR. Outcomes analyzed were the birth weight, gestational age at labor, Apgar score at 1and 5 min, the ratio of NRDS, the ratio of ICH and neonatal death, etc. Results Ten trials were included. Nine trials (576 patients) compared L-arginine with either placebo or no intervention. In the L-arginine treatment groups of the L-arginine trials, there was a significant increase in fetal birth weight (SMD 0.41, 95 % CI [0.24, 0.58]), gestational age (SMD 0.30, 95 % CI [0.07, 0.54]); L-arginine treatment group have a significant reduction in the ratio of neonatal respiratory distress syndrome (P = 0.009), intracranial hemorrhage of fetuses (P = 0.002), but the number of included studies and people on these outcomes are small. As only one trial (41 patients) compared sildenafil citrate with placebo, it was too small for reliable conclusions about possible differential effects could be drawn. Conclusions The results of this meta-analysis showed that L-arginine increased birth weight and prolonged gestational age at labor of IUGR fetuses. However, further large-scale RCTs are needed to adequately assess the effect of L-arginine and Sildenafil citrate on clinical outcomes, because the number of study may be small.